Prevention and Modern Treatment of Fatty Embolism in Traumatological Patients (Eurasian Medical Research Periodical, 2023)
A fat embolism is a multiple occlusion of blood vessels by lipid globules. In this article highlights of prevention and modern treatment of fatty embolism in traumatological patients